METODE PEMBUATAN ANTIPROLAKTIN PADA HEWAN COBA KAMBING LOKAL SEBAGAI PENGHAMBAT PROSES RONTOK BULU PADA AYAM ARAB PETELUR - Erma Safitri (The East Java Biological Society, 2005)
Anti-prolactin has a specific activity against prolactin. It neutralizes prolactin action in circulation. The effect of such neutralization is the inhibition of feather fall off process, so that hens may be able to produce eggs again. Anti-prolactin can be produced by injecting prolactin isolate from blood serum of arabic hens in feather fall off-phase into local goat. Prolactin isolate was immunized to local goat to produce anti-prolactin. Six local goats were divided into 2 groups. The first group comprised 1 goat immunized with PBS, and the second one was immunized with prolactin isolate in CFA and subjected to booster with prolactin isolate in IFA twice. The formation of anti-prolactin and the highest titer was detected using indirect ELISA. The results of this study showed that (1) Anti-prolactin could be produced in goat from the prolactin isolate of feather fall off-phase arabic hens blood serum; (2). The first emergence of Antiprolactin was at the first bleeding after immunization of prolactin isolate in CFA and first booster in IFA. The highest titer was found at eleventh bleeding after the third booster with prolactin isolate in IFA.